Pulpal temperature rise: Evaluation after light activation of newer pulp-capping materials and resin composite - Jash Lakhani; Vineet Agrawal; Rajesh Mahant; Sonali Kapoor; Dipak Vaghamshi; Arpit Shah (Wolters Kluwer Medknow Publications, 2018)
Background: To evaluate temperature changes in pulp chamber during light activation of newer pulp- capping materials and composite resin using light-emitting diode. Materials and Methods: A standardized Class I cavity was prepared in 80 extracted, intact, noncarious mandibular first molars, keeping remaining dentin thickness of 0.5 mm. The teeth were divided into four groups of 20 teeth each. Following this, apical third of the mesial root of each tooth was cut and a K type thermocouple attached to digital thermometer was inserted into pulp chamber from the sectioned mesial root. Whole assembly with teeth was suspended in water bath with constant temperature at 37°C. The previously divided teeth in four groups, were lined with Calcimol LC (Group A), Activa (Group B), TheraCal LC (Group C), and Ionoseal (Group D), followed by 3 increments of Filtek Z350 × T universal restorative. The temperature rise following light activation of pulp-capping material, bonding agent, and composite was noted. Results: The temperature rise in the pulp chamber after light activation of Activa was highest among all pulp-capping materials, followed by teeth lined with Calcimol LC, Ionoseal, and least in teeth with TheraCal LC. Conclusions: Temperature rise in the pulp chamber after light activation of newer pulp-capping materials and composite was below critical threshold for irreversible pulpal damage. Among all the pulp-capping materials, TheraCal LC showed lowest temperature rise in pulp chamber.